Gestión pedagógica del proceso comunicativo intercultural en la formación de estudiantes kichwa hablantes del tercer año de bachillerato del Circuito Co2_B Saquisilí-Cochapamba. Diseño de una estrategia pedagógica comunicativa intercultural. - Aimacaña Chancúsig, Luis Aníbal (2016)
The objective of this research was to design a proposal to improve the communication process among indigenous students of the third year of unified general baccalaureate that Kichwa and the Hispanic teachers of the Cochapamba Educational Unit through the forming of an intercultural communication manual; This due to the problem surrounding the pedagogical management of the communication that was handled in this environment since it had deficiencies and had no defined structure to provide a suitable working environment for teachers and students. The theoretical basis was based on the principles and visions of intercultural education, as well as on educational theories. It referred to the semiological, linguistic processes to determine the noise that motivates the visions that educators have on the basis of Western knowledge versus the circular way of thinking of the inhabitants of the Andes, from their worldview. Cosmic intercultural communication is the strategic point that acts between planning and executing the correct intercultural educational process. It was observed the objectives of the institution that should be in accordance with the mission, vision, policies and philosophy of the institution. The elements that intervene in the human, material and technological levels in the design of the intercultural communication manual made it possible to determine that it is necessary to improve the strategies for future students to homogenize the concrete of the mother tongue, with the abstraction of the Spanish language was observed That there are very different visions of conceiving the world when it penetrates the meaning and signifier of the abstract terms of these future high school students. The theoretical and practical part of this research is the management within the philosophical approach of the main theories of education, communication and interculturality. Taking care that they have strict relation with the variables.